Gum acacia capped ZnO nanoparticles, a smart biomaterial for cell imaging and therapeutic applications. (30th July 2020) - Bera, Debbethi; Pal, Kunal; Mondal, Dheeraj; Karmakar, Parimal; Das, Sukhen; Nandy, Papiya
Abstract: The zinc oxide nanoparticles (ZnONPs) have gained prominence in different biomedical applications nowadays. The phytochemical mediated synthesis of ZnONPs (green synthesis) is cost-effective, facile and generates negligible hazardous impact. In the present study we have utilised the leaf extract of abundantly available well known medicinal plant, Ocimum sanctum (Tulsi) for the phytosynthesis of ZnONPs via a facile process. Gum acacia, a widely recognised natural polymer was used as a capping agent of the biogenic ZnONPs in order to enhance its bioavailability and its therapeutic efficacy. These nanoparticles were tagged with a fluorescent dye, rhodamine-B to observe the cellular imaging applications. The nanoparticles were characterised by different biophysical methods like UV–vis spectroscopy, XRD, FTIR and FESEM for confirmation of their successful synthesis and their antibacterial and anticancer efficacy was then validated. The result clearly suggests that these nanoparticles are able to induce the oxidative stress in both eukaryotic and prokaryotic cells which in turn is responsible for their efficacy against both the pathogenic bacterial strains and hepatocellular cancerous cells. Moreover, these nanoparticles possess pH responsive behaviour and hence it fulfils the essential criteria of cancer therapeutic delivery system. Furthermore, these rhodamine-B tagged nanoparticles are endowed with fluorescence property which can be utilised for bioimaging applications. These nanoparticles could be conjugated with cancer specific targeting ligands in the future that could further augment their therapeutic and diagnostic credentials. Therefore, these nanoparticles could truly emerge as unique promising multifunctional therapeutic intervention in the near future.